2020
DOI: 10.1002/ctm2.4
|View full text |Cite
|
Sign up to set email alerts
|

A four‐factor immune risk score signature predicts the clinical outcome of patients with spinal chordoma

Abstract: Background Currently, the measurement of immune cells in previous studies is usually subjective, and no immune‐based prognostic model has been established for chordoma. In this study, we sought to simultaneously measure tumor‐infiltrating lymphocyte (TIL) subtypes in chordoma samples using an objective method and develop an immune risk score (IRS) model for survival prediction. Methods Multiplexed quantitative immunofluorescence staining was used to determine the TIL levels in the tumoral and stromal subareas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 58 publications
2
33
1
Order By: Relevance
“…Cox proportional regression hazard models were used to identify potential independent prognostic variables, and factors significant in univariable analysis were enrolled in the multivariable analysis. The bootstrap resample analysis with 1,000 repeats (24), which was widely used to test the reproducibility of survival data via randomly sampling patients from the same cohort, was performed to validate our results (25)(26)(27). Receiver operating characteristic (ROC) curve analysis was applied to evaluate the prognostic capacity of these inflammatory markers for 3-year and 5-year OS.…”
Section: Discussionmentioning
confidence: 99%
“…Cox proportional regression hazard models were used to identify potential independent prognostic variables, and factors significant in univariable analysis were enrolled in the multivariable analysis. The bootstrap resample analysis with 1,000 repeats (24), which was widely used to test the reproducibility of survival data via randomly sampling patients from the same cohort, was performed to validate our results (25)(26)(27). Receiver operating characteristic (ROC) curve analysis was applied to evaluate the prognostic capacity of these inflammatory markers for 3-year and 5-year OS.…”
Section: Discussionmentioning
confidence: 99%
“…Chordomas have extensive interactions with the immune system that may help to predict tumor aggressiveness, responses to existing therapies and the development of novel treatments ( Figure 1 ). Zou and colleagues have studied this interaction extensively, specifically in regard to the PD-1/PDL-1 pathway [ 18 , 19 , 20 , 21 ]. In their initial investigations, they reported that the expression of PD-L1 in tumor tissue was associated with advanced chordoma stages and higher levels of tumor-infiltrating lymphocytes (TIL), whereas PD-L1 expression on TIL was associated with improved local recurrence free survival (LRFS) and overall survival [ 18 , 19 ].…”
Section: Chordoma Immune Microenvironmentmentioning
confidence: 99%
“…A few authors have proposed immune-based scoring systems for chordomas to help to predict tumor aggressiveness and outcomes [ 19 , 21 , 26 ]. One study found that in their proposed scoring system of cells by levels of CD3 + and CD8 + TIL in the tumor interior, higher levels of TILs were associated with increased LRFS and overall survival [ 18 ].…”
Section: Chordoma Immune Microenvironmentmentioning
confidence: 99%
“…These patients received curative tumor excision and follow-up information was updated in April 2019. Patients selection fulfilled comparable baseline, treatment and follow-up characteristics to that of the training population (Supplementary Table 1) (22). Sample size in validation group was estimated in advance by a power calculation (23), and minimum of 45 patients were required to show difference with a power of 80%, b error of 0.2, and a error of 0.05.…”
Section: Patientsmentioning
confidence: 99%
“…A total of 114 patients (54 in the training and 60 in the validation cohort) were included. Patient characteristics were recently communicated by our group (22) Table 1). All chordoma cases belonged to classic pathology type.…”
Section: Clinical Characteristicsmentioning
confidence: 99%